Instrumental swallowing assessment in adults in residential aged care homes: Practice patterns and opportunities. (8th August 2022) - Birchall, Olga; Bennett, Michelle; Lawson, Nadine; Cotton, Susan M.; Vogel, Adam P.
Abstract: Objective: To describe practice patterns in the use of instrumental swallowing assessment (ISA) for older adults in residential aged care homes (RACHs). Methods: A retrospective audit of medical records of residents living in RACHs in Melbourne, Australia to extract data on speech‐language pathologist (SLP) involvement, indications for ISA and ISA practice patterns. Results: Medical files of 323 residents across four Melbourne facilities were reviewed. 36% ( n  = 115) of residents were referred to SLP for swallowing assessment. Referral to SLP was related to length of stay ( U  = 7393.00, p  < 0.001), dementia status ( χ 2 [1] = 7.06, p  = 0.008), texture modification ( χ 2 [1] = 93.34, p  < 0.001) and an existing dysphagia diagnosis ( χ 2 [1] = 112.89, p  < 0.001). There were no referrals for ISA and no instances of ISA being used. Among 115 residents who were referred to SLP for swallowing assessment, there were 33 instances where ISA might be clinically relevant according to ISA indicators. Conclusions: Instrumental swallowing assessment is not being used for the management of swallowing in RACHs in Australia despite a clinical need for ISA and a potential role for ISA to improve swallowing care quality. Lack of timely ISA may fail to meet the complex health‐care needs of older adults living with dysphagia in RACHs, increasing their vulnerability to complications of dysphagia and its management.